Unraveling gene expression: a beginner’s guide from chromatin modifications to mRNA export in Saccharomyces cerevisiae - Joan Serrano-Quílez; Susana Rodriguez-Navarro (Nucleus)
Understanding gene expression requires grasping its multi-step processes, from chromatin remodeling to mRNA export. This manuscript provides an accessible entry point for PhD students and junior postdocs beginning research in this area, using yeast as a model organism. We present a beginner-friendly overview of gene expression, emphasizing the dynamic interplay between chromatin modifications, transcription, mRNA processing, and export. Key topics include chromatin organization, with a focus on H2B ubiquitylation and H3 methylation crosstalk; transcriptional control by RNA polymerase II, including initiation, elongation, and termination; and the export of mRNAs via Mex67–Mtr2, adaptor proteins, and the TREX and TREX-2 complexes at the nuclear pore complex. Relevant examples from yeast genetics, biochemistry, and structural biology illustrate each step. This overview aims to equip new researchers with foundational knowledge and provides references to key studies, current challenges, and open questions in the regulation of gene expression.